Synthesis, Characterizationa Performance of Polysulfone/Cellulose Acetate Phthalate/ Polyvinylpyrrolidone (Psf/CAP/PVP) Blend Ultrafiltration Membranes - Asmadi, Ali @ Mahmud (2013)
Polysulfone (PSf) is an important class polymer that has been most widely used in the manufacture of synthetic asymmetric ultrafiltration membranes. However, the main disadvantage of PSf membrane is due to its hydrophobic characteristic which in turn fouled the membranes. In practical application of UF systems, membrane fouling is a serious problem that causes high cost energy, operation, and maintenance. Polymer blend is a simple and an efficient method for designing new materials to improve performance of the hydrophobic membranes. The polymer blend is a proven tool to obtain new types of UF membrane, which has better hydrophilicity compared to the original membranes. Cellulose acetate phthalate (CAP) is one of the potential hydrophilic organic polymers that can be used and explored in PSf polymer blend technique to improve hydrophilicity and performance of PSf membranes. PSf/CAP blend membranes with blend composition of 95/5, 90/10, 85/15 and 80/20 wt% of total polymer concentration in the membrane casting solutions were developed via wet phase inversion process. The effect of CAP composition on characteristics, morphology and performance of PSf/CAP blend membranes were investigated. The hydrophilicity of the PSf/CAP blend membranes were improved evidently by blending with CAP. Based on BSA protein separation performance study, the PSf/CAP blend ultrafiltration membrane which contains 10 wt% of CAP shows the best performance membrane due to its high productivity and separation performance as well as it has good membrane characteristics in terms of high hydrophilicity properties, pore properties and membrane morphological structure. The effect of polyvinylpyrrolidone (PVP) additives in the range of 1 to 5 wt% on the best PSf/CAP blend membranes was studied. The results revealed that an addition of 1 to 3 wt% of PVP additive formed membrane with small average pore size and low MWCO due to the strong interpenetrating network between PSf-CAP-PVP and consequently increased protein rejections. Further increment of PVP additive promoted PVP leached out during wet phase inversion process and formed membranes with big pore size and high MWCO. These membranes had high permeate flux but low rejection of proteins. The PSf/CAP/PVP blend membrane that contains 3 wt% of PVP was selected as the best high performance membrane. Further, there were five different shear rates (42.0, 52.5, 70.0, 105.0 and 210.0 s -1) applied during fabrication process of PSf/CAP/PVP blend membranes by using the best PSf/CAP/PVP dope formulation. The experimental results showed that an increase in shear rate from 42.0 to 105.0 s-1 decreased the water content, porosity and permeability of the membranes. Further increment of shear rate to 210.0 s-1 increased the water content,porosity and permeability of the membranes due increased in porous structure of PSf/CAP/PVP membrane and a decrease in membrane thickness. In terms of BSA separation performance, the PSf/CAP/PVP blend membranes fabricated at the shear rate of 105.0 s-1 showed the best performance due to high rejection of BSA at favorable permeation flux of BSA protein solution. In an evaporation time study, the PSf/CAP/PVP blend membranes fabricated at shear rate of 105.0 s-1 were introduced to evaporation time of 5, 10, 15 and 20 s before immersed in a coagulation bath. The results showed that the effects of evaporation time significantly changed the properties and morphological structures of the PSf/CAP/PVP blend membranes. In this experiment study, PSf/CAP/PVP blend membrane which was fabricated at evaporation time of 10 s exhibited the best performance membrane due to high membrane productivity and separation ability.